The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/mi12030227
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistance Reduction Induced with CO2 Laser Single Line Scan of Polyimide

Abstract: We conducted a laser parameter study on CO2 laser induced electrical conductivity on a polyimide film. The induced electrical conductivity was found to occur dominantly at the center of the scanning line instead of uniformly across the whole line width. MicroRaman examination revealed that the conductivity was mainly a result of the multi-layers (4–5) of graphene structure induced at the laser irradiation line center. The graphene morphology at the line center appeared as thin wall porous structures together w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Micro-Raman scattering characteristics with the ratio I 2D/IG of 0.3-0.5 [23] indicates that graphene has a multilayer structure of 4-5 layers for the electrically conductive layer formed on the polyimide surface. Moreover, they're shown that:…”
Section: D /I G I 2d /I G Ratios and Sheet Resistance Correlationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Micro-Raman scattering characteristics with the ratio I 2D/IG of 0.3-0.5 [23] indicates that graphene has a multilayer structure of 4-5 layers for the electrically conductive layer formed on the polyimide surface. Moreover, they're shown that:…”
Section: D /I G I 2d /I G Ratios and Sheet Resistance Correlationsmentioning
confidence: 99%
“…Raman spectra of: left -graphene oxide (GO) and highly reduced laser-scribed graphene (hr-LSG); right -LIG, polyimide (PI). Adapted with permissions from references [21][22][23]. stacking of graphene sheets along c-axis * The Raman spectrum of crystalline graphite has only one Raman peak at 1580 cm À 1 , which is called the G band.…”
Section: D /I G and I 2d /I G Ratios In Context Of Electroanalysis (S...mentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, it is obviously acceptable that increasing laser power and multiple irradiation are general methods to obtain qualified electrical performance of LIG electrodes with reasonable sheet resistance. [ 36 ] However, there is a trade‐off in this parametric condition to maintain the flexibility and mechanical stability of the LIG‐structured films because the excessive laser power and multiple irradiation generally cause partial damage to the carbon source substrates that substantially affect its mechanical properties. [ 37 ] Therefore, it is important to balance the flexibility and mechanical stability of the electrically high‐performance LIG electrodes by optimizing the physical parameters without the loss of intrinsic properties of the LCP film.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity ratio of D/G indicates an inverse correlation with the degree of graphene crystallinity in the LIG; specifically, a higher D/G implies more numerous defects, lower crystallinity, and thus lower graphitization. Moreover, an intensity ratio of 2D/G > 2 indicates high-quality, single-layer graphene [51]; if 2D/G < 0.6, the produced graphene contains more than four layers. That is, a lower 2D/G ratio indicates a greater number of graphene layers.…”
Section: Raman Spectroscopy Resultsmentioning
confidence: 99%